(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Language acquisition is a natural cognitive process that is long-term and complex of human activities. It is a sophisticated structure that makes people different from other beings. From an early age, the human brain struggles to enhance communicative capabilities. Language mastery develops step by step starting with the baby’s crying gradually growing into short utterances and eventually producing meaningful speech. Subtleties in the child’s language development have been a focus of numerous studies and collections of research.